Pemberdayaan Pelaku UMKM Menuju Pajak Melek Digital melalui Sosialisasi dan Implementasi Sistem Coretax sebagai Upaya Peningkatan Literasi Perpajakan Digital - Idris, Hariany; Ginting, Chris Dayanti Br.; Rahman, Ahmad Nashiruddin Mushoddiq; Ryketeng, Masdar; Samsinar, Samsinar (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
The community service activity aims to socialize and implement the Coretax System as an effort to increase digital tax literacy for micro, small, and medium enterprises (MSMEs). The service method uses an educational and participatory approach. The results of the community service activity enable MSMEs to understand the benefits of Coretax in simplifying tax administration obligations while raising awareness of the importance of tax compliance as a form of contribution to national development. Overall, this activity emphasizes the importance of synergy between the academic world, community institutions, and tax authorities in strengthening tax literacy and compliance through digital innovation.